2020
DOI: 10.1186/s13229-020-0320-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in human stem cell-based modeling of Tuberous Sclerosis Complex

Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant disorder characterized by epilepsy, intellectual disability, and benign tumors of the brain, heart, skin, and kidney. Animal models have contributed to our understanding of normal and abnormal human brain development, but the construction of models that accurately recapitulate a human pathology remains challenging. Recent advances in stem cell biology with the derivation of human-induced pluripotent stem cells (hiPSCs) from somatic cells from patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…As a complement to these animal models, human stem cell-based models of TSC and other mTORopathies have emerged over recent years due to advances in human stem cell and genome engineering [164-168]. These systems can capture human- or patient-specific aspects of cell biology, genetics, and brain development and thus provide an important complement to mouse models.…”
Section: Animal Models Of Mtoropathiesmentioning
confidence: 99%
“…As a complement to these animal models, human stem cell-based models of TSC and other mTORopathies have emerged over recent years due to advances in human stem cell and genome engineering [164-168]. These systems can capture human- or patient-specific aspects of cell biology, genetics, and brain development and thus provide an important complement to mouse models.…”
Section: Animal Models Of Mtoropathiesmentioning
confidence: 99%
“…A few comprehensive overviews of human cell models with TSC1 and TSC2 knockouts in iPSCs, ESCs, and 3D organoid cultures were published recently [138,139]. Most studies are based on patient-specific iPSCs generated from TSC1 or TSC2 mutation carriers and indicate an overall decrease in neurons comparative to their respective controls [140][141][142][143].…”
Section: Cell Models Of Mtoropathies 411 Tscmentioning
confidence: 99%
“…Cell specificity, mutation load, and mutation timing during brain development likely give rise to the diverse neuropathological presentations. Recent evidence from in vitro cell cultures and organoid models of TSC revealed that mTORC1 activity during cortical development is tightly controlled, and mTORC1 suppression is required for proper neurogenesis ( 51 ). Of note, mTORC1 hyperactivity promotes gliogenesis, likely explaining the increased number of glia in tubers ( 52 56 ).…”
Section: Introductionmentioning
confidence: 99%